PENERAPAN MODEL KOOPERATIF STAD UNTUK MENINGKATKAN PENGUASAAN KOSAKATA DAN POLA KALIMAT BAHASA JEPANG DI KELAS XI IPA 5 SMAN 2 SINGARAJA TAPEL 2021/2022 - Gede, Putra Sastrawan (Universitas Negeri Jakarta, 2022)
This research aims to determine (1) the increase in mastery of vocabulary and sentence patterns in Japanese after implementing the STAD Cooperative learning model in Class . The subjects of this research were 25 students of class XI IPA 5 SMA Negeri 2 Singaraja. Data collection methods are carried out through involved observation, tests and questionnaires. The research data was analyzed descriptively, quantitatively and qualitatively. The results of the research show (1) the STAD Cooperative learning model to improve mastery of vocabulary and sentence patterns for students in class in post-test I it was 47.1, in post-test II it was 72.0, and post-test III it was 85.9. (2) Student responses to the implementation of the STAD Cooperative learning model are positive. Most students felt helped in learning activities, student motivation increased, students felt an increase in mastery of vocabulary and sentence patterns, students liked the teaching technique using the STAD Cooperative model, and students did not find it difficult to understand Japanese vocabulary or sentence patterns during learning.